KONTESTASI IDENTITAS (Studi Analitis Terhadap Gikiri dan Kekristenan di Kao Halmahera Utara) - , Agnes Megy Takaendengan, Prof. Dr. Irwan Abdullah ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Gikiri an indigenous religion of Kao revived during ethnic conflict in Kao on 1999. The conflict entangled Native Kao and New comer Makian who lived in Malifut the land of Kao. Even though conflict brought high tension of socio-politic, economy and cultural for both ethnic groups, For Kao people, conflict as a media of contestation in which reconstructed Kao`s cultural identity in Gikiri. It is a Kao`s indigenous religion that has been alienated and marginalized since Zending era that has introduced them with Christianity. In Protestant-Kao` socio-religious mapping put Christianity and Gikiri in a binary opposition in which Christianity is a truth religion that could bring human to salvation, goodness and peacefulness. On the other hand, Gikiri is infidel (kafir) and related to evil spirits. This research aims to analyze socio-ethnic conflict which became a field of struggle for agents of Gikiri, Christianity and the State at that time that were in contestation to each other by using such strategies of symbolic struggle to gain position, power and capital. However, in the field of conflict Gikiri played important role to help Kao people to overcome the crises. Gikiri`s power was used during the conflict to represent social, culture and âreligiousâ identities of Kao as a native people to against Malifut people. That time was a precious moment for its revival in Protestant-Kao community. In this case, identity is an unstable construction